Târîh-i Cevdet - Cevdet Paşa, 1823-1895. (Ankara Ankara Ankara)
6 cilt 7 kitapta (1. c. xiii, 436 sayfa ; 2. c. 1. kitap xiv, 412 sayfa ; 2. c. 2. kitap sayfa 413-1025 ; 3. c. xix, 487 sayfa ; 4. c. xiv, 449 sayfa ; 5. c. xi, 553 sayfa ; 6. c. xiv, 514 sayfa)